Technological competency as caring in nursing: A description, analysis and evaluation of the theory - Krel Cvetka; Vrbnjak Dominika; Bevc Sebastjan; Štiglic Gregor; Pajnkihar Majda (Sciendo, 2022)
When introducing and using technology in nursing, there is a danger that too much focus is placed on technology over caring for patients. The 'Technological competency as caring in nursing' theory can facilitate technology in caring, but the theory needs to be described, analysed and evaluated before it is used. The purpose of the literature review was to determine the possibility of applying the theory in education, research and practice, and whether the theory could be used to guide research into the use of electronic nursing record systems.